Peningkatan Kemampuan Membaca Al-Qur’an Peserta Didik Melalui Penerapan Metode An-Nahdliyah - Zaeni, Abu (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Learning the Qur'an is an obligation that must be undertaken and nurtured by every Muslim individual. This forms the fundamental reasoning behind prioritizing the skill of reading the Qur'an as the main focus in Islamic education. One of the approaches that can be employed in Qur'anic learning is the An-Nahdliyah method. This method emphasizes conformity and regularity with the rhythm of recitation. The objectives of this research are to gain an overall understanding of the implementation of the An-Nahdliyah method at MI NU Assalaam in Wonorejo Barat and to identify the supporting and hindering factors in Qur'anic learning at MI NU Assalaam in Wonorejo Barat, Kampungbaru Kepung, Kediri. In this study, a qualitative approach was utilized with data collection techniques involving observation, interviews, and documentation, integrated to obtain comprehensive data. The method of data analysis employed was qualitative descriptive. The research findings indicate that: (1) the implementation of the An-Nahdliyah method at MI NU Assalaam involves the use of materials aligned with the targeted outcomes through demonstration, drill, and lecture methods, with adjustments in the allocated class time as specified in the instructional guidebook. (2) Supporting factors in Qur'anic learning at MI NU Assalaam encompass reading intelligence, students' attitudes and interests, study habits, knowledge or experience in reading, and the students' overall condition. Hindering factors in Qur'anic learning at MI NU Assalaam include limited reading abilities, psychological factors, and external influences from family and the environment.